Relationship Between Absorptive Capacity and Innovation Ambidexterity: Mediating Role of Entrepreneurial Orientation - HAMDI, Rahma (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
The literature in management sciences highlights the importance of entrepreneurial orientation as a lever to enhance productivity, competitiveness, and strengthen the position of companies. Globally, businesses are increasingly investing in developing their innovation capabilities to meet the demands of the digital economy and the "Smart Life" era. In this context, the absorptive capacity for knowledge, as well as the ambidexterity of exploration and exploitation, play crucial roles. However, current research does not yet clearly specify the causal links between these concepts. This study aims to determine how absorptive capacity influences innovation ambidexterity, considering the mediating role of entrepreneurial orientation.Based on a positivist epistemological approach, this work relies on a literature review and the results of three exploratory studies. This leads to an explanatory model of the relationships between absorptive capacity and innovation ambidexterity, tested on 258 entrepreneurs and project holders in the ICT sector in Tunisia, operating within a "Smart City." The results show that absorptive capacity enhances innovation ambidexterity, with a significant mediating role of entrepreneurial orientation.Key words: Absorptive capacity, ambidexterity, innovation exploration, innovation exploitation, entrepreneurial orientation.